TOBACCO LEAVES EXTRACT (Nicotiana tabacum) AS A NATURAL CORROSION INHIBITOR OF CARBON STEEL - Micha Mahardika; Ninik Triayu Susparini; Isna Lailatusholihah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2024)
Tobacco leaves have great potential as corrosion inhibitors due to the chemical compounds present in tobacco leaf extracts that play a role in inhibiting the corrosion rate, specifically tannins. The objective of this study was to determine the corrosion rate value and efficiency of tobacco leaf extract as an inhibitor on corrosion coupons exposed to a sulfuric acid solution. The initial step involves preparing smooth corrosion coupons and tobacco leaves. The tobacco leaves were prepared by extracting them through a maceration method using ethanol solvent over a 5-day period. A corrosive media solution of 1 M H2SO4 and corrosion coupons measuring 0.1 x 1.3 x 7.65 cm were also prepared. Subsequently, both the corrosion coupons and tobacco leaf extract were soaked in an acidic solution for the initial sample. The highest tannin content was found in the tobacco leaf extract using ethanol solvent (in a ratio of 1:6), yielding 31.35%. At the highest concentration of 800 ppm, the corrosion rate of the tobacco leaf extract was measured at 17.36 mm/year. Additionally, the inhibition efficiency of the tobacco leaf extract in the corrosive medium, a 1 M H2SO4 solution, reached 89.82% at a concentration of 800 ppm, with a soaking time of 5 days.